Evaluasi Proses Seleksi Karyawan dalam UMKM Kuliner : Studi Kasus pada Usaha Seblak Prasmanan Jeletot Medan - Harmen, Hilman; Jesica Juliana Situmeang; Raissa Fathia; Arditha Chayani Purba; Aulia Dinda Utami; Fatiman Azzahra Saragih; Febrian Alexa Sampang Ate Tumangger; Ahmad Hidayat Pandia (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
Micro, Small, and Medium Enterprises (MSMEs) in the culinary sector face significant challenges in effective employee selection processes. This research aims to evaluate the effectiveness of employee selection processes at Seblak Prasmanan Jeletot Medan, identify obstacles faced, and provide recommendations for more effective selection strategies. Through a qualitative approach with a case study method, data were collected through in-depth interviews and direct observation. The results show that selection processes that rely solely on social media, selection criteria that prioritize domicile over skills, limited workforce on night shifts, and strict age restrictions have led to high turnover rates, workload imbalances, and decreased service quality. The research recommends expanding selection methods, balancing selection criteria, adding workforce on night shifts, and reviewing age restrictions to improve the effectiveness of employee selection, which in turn will support business sustainability and growth.